Evaluation of potentially available nitrogen by biological and chemical methods in soil cultivated with maize in succession to cover crops - Bettiol, Aline Carla Trombeta [UNESP]; Braos, Lucas Boscov [UNESP]; Lopes, Ivã Guidini [UNESP]; Andriolli, Itamar [UNESP]; Ferreira, Manoel Evaristo [UNESP]; da Cruz, Mara Cristina Pessôa [UNESP] (Taylor & Francis, 2022)
Estimating mineralization rates is one of the best ways to predict N availability over time. However, different methods can lead to distinct predictions, especially when different production systems are used. The aim of this study was to compare biological and chemical methods commonly used to estimate the potentially available N in a soil cultivated with maize in succession to cover crops and N fertilization. The experimental area has been cultivated with cover crops (jack bean, velvet bean, millet and spontaneous vegetation) and N fertilization (0, 60, 120 and 180 kg N ha−1) since the year 2000 in a split-plot design with cover crops as the main treatments and N rates as secondary treatments. The biological evaluation of N mineralization was performed by means of an aerobic incubation of soil samples, while the chemical methods were either by the use of saline ((Ca(H2PO4)2, CaCl2, KCl) and Illinois soil test and direct steam distillation (DSD). Soil C and N contents were not affected by the cover crops, even after sixteen years of cultivation. The utilization of N by maize plants was affected by cover crops, especially for jack bean, while N fertilization led to a maximum absorption point, estimated in 158 kg N ha−1. The methods for evaluating the potentially available N behaved differently among treatments. The DSD method has significantly correlated with maize N uptake and yield, which demonstrates that it was the most promising method to estimate the potentially available N, although it is not yet calibrated for all agricultural systems.
Keywords: mineralization; N dynamics; soil fertility; winter crops